β-glucans and eicosapolyenoic acids as MAMPs in plant–oomycete interactions: past and present - Robinson, Sara M.; Bostock, Richard M. (Frontiers in Plant Science, 2015)
Branched β-1,3-glucans and the eicosapolyenoic acids (EP) are among the best characterized oomycete elicitors that trigger innate immune responses in plants. These elicitors were identified over three decades ago, and they were useful in the study of the sequence of physiological, biochemical and molecular events that induce resistance in plants. However, in spite of the cross-kingdom parallels where these molecules are well-characterized as immune system modulators in animals, their perception and modes of action in plants remains obscure. Oomycetes are among the most important plant pathogens, responsible for diseases that devastate crops, ornamentals, and tree species worldwide. With the recent interest and advances in our understanding of innate immunity in plants, and the redefining of many of the classical elicitors as microbe-associated molecular patterns (MAMPs), it seems timely and important to reexamine β-glucans and EP using contemporary approaches. In this review, we highlight early studies of β-glucans and EP, discuss their roles as evolutionarily conserved signals, and consider their action in relation to current models of MAMP-triggered immunity.